THE EMERGENCE OF THE SCIENCE OF THE WORD AND ITS PLACE IN THE STUDY OF DOGMATIC ISSUES IN ISLAM (Scientific journal of the Fergana State University, 2024)
This article describes the emergence of the knowledge of the Word, its improvement in the process of discussions between different political and religious sects in Islam and the debates with representatives of other religions, as well as the harmony of the Word and Islamic beliefs.